Post occupancy evaluation on design factor of ablution area in musholla: Shah Alam shopping centers - Raha Sulaiman,; Norhaziqah Ikmal Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Musholla is one of the facilities provided in the shopping malls. In Islam, cleanliness is the main aspect especially when someone wants to pray. The ablution area is one of the important areas that are highly accessible in the Musholla and the importance of providing it is also a part of Islamic virtue as this area is places of cleansing certain parts of the body in a certain order or in Arabic, it called as ‘wudu’. Since there is lack of guideline and document specifically on ablution area, this paper is to give some fundamental criteria for the ablution design guideline. To get the result, this research is to identify the design factors of an ablution area that make comfortable for users in the Musholla. Also, this research is to investigate the effectiveness of the ablution design in the Musholla. For that reason, the observation and data collection has been carried out at selected case studies, which are Mall A and Mall B. Since Malaysia does not have specific guideline for ablution area, the post occupancy evaluation for current ablution design is very important, as it can lead the architects and designers in designing the better ablution area. This research is carried out using quantitative and qualitative approach which are interview session with the local authorities, questionnaire survey to the users, and observation to evaluate the effectiveness of the ablution area at those buildings. The conclusions for this research pointed out that there are several factors should be considered into the ablution design such as size, space arrangement between clean zone and non-clean zone, facilities for Person with Disabilities (PwDs), ergonomic aspects for ablution unit, maintenance and security. Hence, the recommendations on the fundamental criteria for an ablution design guideline are provided.